Additive manufacturing of pure copper using ultrashort laser pulses - Kaden, Lisa; Matthaeus, Gabor; Ramm, Roland; Ullsperger, Tobias; Seyfarth, Brian; Nolte, Stefan (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
Here we present laser aided additive manufacturing of pure copper parts using ultrashort laser pulses. The process is based on the powder bed fusion of pure copper powder with grain sizes in the range of 5 μm - 15 μm. For processing, a fiber laser system delivering 500 fs pulses at a wavelengths of 515 nm was used. Robust 3D printed parts are generated featuring a high degree of resolution. The fabricated copper samples were characterized in terms of morphology, density distribution, thermal and electrical conductivity. The inner structure is revealed by x-ray computed tomography measurements.
CRIS-Team Scopus Importer:2023-04-20
Keywords: 3D printing; Additive manufacturing; Copper; Powder bed fusion; Selective laser melting; Ultrashort laser pulses; X-ray computed tomography